Integrase strand transferase inhibitors: the preferred antiretroviral regimen in HIV-positive renal transplantation. (April 2017) - Azar, Marwan M; Malinis, Maricar F; Moss, J; Formica, Richard N; Villanueva, Merceditas S
In the era of antiretroviral therapy, people living with HIV/AIDS live longer and are subject to co-morbidities that affect the general population, such as chronic kidney disease. An increasing number of people living with HIV/AIDS with end-stage renal disease are candidates for renal transplantation. Prior experience demonstrated that HIV-positive renal transplant recipients had acceptable survival but graft survival was decreased and rejection rates were increased, possibly due to suboptimal management of immunosuppressive medications in the face of drug interactions with antiretroviral therapy, particularly protease inhibitors and non-nucleoside reverse transcriptase inhibitors. Integrase strand transferase inhibitors are advantageous since they avoid drug–drug interactions with immunosuppressive drugs such as calcineurin inhibitors. We report clinical outcomes of 12 HIV-positive patients who underwent 13 kidney transplantations at our institution between 2000 and 2015. Cumulative survival was 75%, one-year and three-year survival were 100% and 63%. Integrase strand transferase inhibitor-based regimens were used in nine patients, of which eight survived. In patients on integrase strand transferase inhibitor, there was 100% graft survival and two had allograft rejection. In contrast, graft failure occurred in three patients on non-integrase strand transferase inhibitor-based regimens. Based on our study findings and on previously published data, we conclude that integrase strand transferase inhibitor-based therapy, preferably instituted prior to transplantation, is the preferred antiretroviral regimen in HIV-positive renal transplantation.